THE COMMERCE IN THE SMALL TOWN PIRAJU/SP - Pereira, Thiago Henrique Valério; Rosário Brumes, Karla (Geografia em Atos (Online), 2013)
This paper intends to analyze the dynamics and spatial organization of commerce and its connection with the coffee in the city of Piraju, inside of São Paulo. o develop the research we have adopted techniques such as interviews with traders and local merchants as well as photographs to better understand urban space of Piraju. Lastly, the work is divided into three parts: a theoretical analysis of commerce and small town, the behavior of commerce, the role of the free market and the ratio of commerce of Piraju with the surrounding municipalities.